Angiopoietin-like protein 4 and cardiovascular function in COPD. Issue 1 (31st October 2016) - Waschki, B; Kirsten, AM; Holz, O; Meyer, T; Lichtinghagen, R; Rabe, KF; Magnussen, H; Welte, T; Watz, H; Janciauskiene, S
Abstract : Introduction: The coexistence of chronic obstructive pulmonary disease (COPD) and cardiovascular disease (CVD) is frequent and might be inter-related through inflammation-related processes reflected by specific markers. Here, we studied angiopoietin-like protein 4 (ANGPTL4), an upcoming cardiovascular marker, in stable COPD, and its relationship to cardiovascular function with respect to well-known CVD risk factors. Methods: In a prospective COPD cohort study, we investigated serum ANGPTL4 levels, vascular status (ankle–brachial index (ABI)) and cardiac function (N-terminal pro-B-type natriuretic peptide (NT-proBNP)) as well as airflow limitation, objectively measured physical activity, the metabolic syndrome, high-sensitive C reactive protein (hs-CRP) and other CVD risk factors at 2 time points. We initially studied 74 stable COPD patients and 18 controls. For internal validation, we additionally studied 160 COPD patients of a former visit. Results: ANGPTL4 was significantly elevated in COPD patients compared with controls (p=0.026). After correction for traditional CVD risk factors, including hs-CRP, higher levels of ANGPTL4 were independently associated with lower ABI (p=0.023) and higher NT-proBNP (p<0.001). These findings were confirmed in the internal validation analysis, which included echocardiographic assessments. Conclusions: Serum ANGPTL4 is independently associated with cardiovascular function in COPD and might qualify as a biomarker reflecting a pathogenic link between COPD and CVD.